Capacity Building: Home and Away - Peter Hudson; Rebecca Spooner Lane; Karen Dooley (UUM Press, 2007)
Many countries are at pivotal points for reforming their education systems, particularly Asian countries moving into English as the medium instruction. The Ministry of Education Malaysia aims to reach its government’s Vision 2020 for education reform, which includes teaching science education in English. Achieving Vision 2020 requires capacity building for Malaysian teaching institutes and their lecturers. The capacity building in this study involved professional development on specific preservice teacher education units conducted through Australian and English universities. Thirty-one Malaysian lecturers from two institutes were involved in professional development with three Australian university lecturers associated with a new primary science education degree. In addition, 96 Malaysian preservice teachers were co-taught by both the Malaysian and Australian lecturers over a two-week period, which provided lecture and tutorial demonstrations on science education, English, and human development psychology. This paper highlights capacity building in the areas of teaching and learning for Malaysian teaching institutes and the affiliated Australian university. Malaysian and Australian lecturers and the Malaysian preservice teachers gained an opportunity to refine their pedagogical knowledge and content knowledge with linkages to current theories (i.e., on science education, English, and human development psychology). International collaboration appeared to enhance teaching and learning programs by globalizing coursework, and presented potential for collaborative research.